The Role of Coping Mechanisms in Nurses’ Distress in the Hospital Emergency Department - Angdriany, Yeny; Erwandi, Dadan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Nurses working in hospital emergency departments are healthcare professionals at high risk of experiencing distress due to intense work pressure, emotional burden, and unpredictable working conditions. This situation may affect nurses’ mental and physical health as well as their performance. Therefore, effective coping mechanisms are required to manage distress, maintain well-being, and ensure the quality of healthcare services. This study aimed to analyze the role of coping mechanisms in addressing distress experienced by nurses in hospital emergency departments. The study employed a systematic literature review approach. Articles were searched through the Google Scholar and ScienceDirect databases using the keywords coping mechanism, distress, nurse, and hospital emergency unit. From a total of 48,117 articles identified, selection was conducted based on the following inclusion criteria: (1) articles published in English or Indonesian, (2) published between 2020 and 2025, and (3) discussing coping mechanisms and distress among emergency department nurses. The selection process consisted of identification, eligibility screening, and full-text review. The final results yielded 12 articles that met the criteria and were analyzed based on research design, methods, measurement instruments, and the alignment between study objectives and findings. From these 12 articles, various coping strategies were identified as effective in reducing distress, including coping-related training and education, psychological interventions, mindfulness, spiritual coping, social support, and social behavioral changes. Several interventions also focused on organizational improvements and the development of compassion skills. In conclusion, coping mechanisms play an important role in reducing distress among emergency department nurses through both individual- and organizational-oriented interventions. The implementation of continuous training and support is essential to strengthen nurses’ coping capacity, create a healthy work environment, and improve the quality of hospital services.Keywords: coping mechanism; distress; nurses; emergency department